Advances in Takayasu arteritis: An Asia Pacific perspective - Danda, Debashish; Manikuppam, Prathyusha; Tian, Xinping; Harigai, Masayoshi (Frontiers in Medicine, 2022)
Takayasu Arteritis (TA) is a rare form of chronic granulomatous large vessel vasculitis that is more common in Asia compared to other parts of the world. Over the past decade, there have been several developments in areas related to genetics, classification, clinical features, imaging, disease activity assessment and management. Several of these works have been done in the Asia Pacific region. The current review summarizes the recent advances in this field.